Missile Injuries to The Spine Local Experience and Review of The Literature - A Hamdan, Thamer.; Chasib, Raed J.; Lui, Darren F. (Clinical Medicine And Health Research Journal, 2024)
Introduction: Missile injuries of the spine particularly the high velocity projectiles are very destructive, leading to real disaster and even death. The incidence has increased recently on both civilian and military troops. The ideas behind writing this article is to shed the light on the seriousness of this type of injury and on the consensus for the ideal treatment depending on our local experience and others experience. Materials and Methods: We review our patient’s files whom had missile injuries related to orthopaedic practice since the last 40 years in public and private hospitals and we also search the web looking for articles discussing missile injuries in orthopaedic practice. We collect complications that observed in our patients and reported in literatures to be mentioned in the results of this review. Results: Missile injuries is the cause of 13-44% of all spinal injury. The cervical lesion is behind complete neurological deficit in 70% of cases. Almost all injuries are stable particularly in the cervical lesion provided that both facet and both pedicles remain intact. Probably pain is one of the commonest complications recorded. Bullets removed did not relieve the pain due to depression. Infection is very much expected after the dirty missile wounds. Neurogenic bladder and urinary tract infection are also possible, meningitis, bone infection, Charcot arthropathy and deformity are all possible. Lead intoxication is a late and very rare complication. The last rare but possible complication is the migration of the missile. Conclusions: Gunshot injury to the spine is becoming more and more prevalent in both military and civilian practice. Probably the absolute indication for surgery is the progressive neurological deficit. A cover of antibiotic is mandatory. A careful search for the instability is mandatory and lastly, Steroids use in spinal missile injuries is controversial.